PENGUNGKAPAN KEUANGAN PERKARA SECARA MEMADAI DALAM LAPORAN KEUANGAN SATUAN KERJA PERADILAN - Muhammad Anis (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
Legal fees are collected and maintained by Supreme Court and the courts underneath it so far still an issue related to the management of accounting and reporting. Based on Surat Edaran Mahkamah Agung Nomor 09 tahun 2008 tentang Pelaporan Penerimaan dan Penggunaan Biaya Perkara pada Pengadilan and Peraturan Mahkamah Agung RI. No. 03 Tahun 2012 tentang Biaya Proses penyelesaian perkara dan Pengelolaannya pada MA dan Badan Peradilan yang berada dibawahnya In these rules have arranged that legal fees in the court aggregately were published periodically and managed effectively, efficiently, transparency and stored in a note upon the financial report of the supreme court. Based on Surat Edaran Mahkamah Agung Nomor 09 tahun 2008, report of legal fees has been running well but not yet shown in the financial statements of the institution. The legal fees become important information that must be reported in in the financial statementsas a form of accountability upon a fee levied and to or received from third party. Keywords: court fees, adequatedisclosure